Activity Test Of Salam Extract (Syzygium polyanthum) On Diabetes Disease Using White Rats (Ratus Novergicus) - Hikmad Elsi Enoni Harefa; Astriani Natalia Br Ginting; Rena Meutia; Nerly Juli Pranita Simanjuntak (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood sugar levels due to impaired secretion or action of insulin. The use of herbal plants such as as salam leaves (syzygium polyanthum) is one of the alternative treatment methods. This study aims to evaluate the effectiveness and optimal dosage of salam leaf extract in lowering blood glucose levels in male rats (Rattus Novergicus) induced by alloxan. A total of 30 rats we divided into six groups: normal control, negative control, positive control (metformin), and three treatment groups with extract doses of 200, 300, and 400 Mg/KgBB. Blood glucose levels were measured on days 15,20,25, and 30. Data were analyzed using ANOVA with a significance level of 95%. The results show that salam leaf extract significantly lowers blood glucose levels, with the most effective dose being 400 Mg/KgBB. This study supports the potential of salam leaves as an effective, safe, and affordable natural antidiabetic agent.